Effect on Human Metabolic Rate of Skin Temperature In An Office Occupant - R. A., Bakar; Norfadzilah, Jusoh; Ahmad Rasdan, Ismail; Tanti Zanariah, Shamshir Ali (EDP Sciences, 2017)
The motivation of this study is to get a better understanding about the real thermal sensation of people in an office environment who undertakes moderate activities. The purpose of this study was to investigate occupant real thermal sensation at three tasks of activities and skin temperature to figure out its impact on thermal sensation in an office environment. All measurements were conducted in a climate chamber. In total, fifteen subjects were participated in three kinds of activities and skin temperatures, which is eleven locations were measured using thermocouple sensors. The results showed that the temperature is the one of the factors which affect metabolic rate. There is a strong linear relationship between these three tasks of activities and metabolic rate with the skin temperature. Furthermore, the results indicate that there was a greater increase thermal sensation when the metabolic rate 1.6. The conclusions of this study can provide some references to set a standard for air conditioning design and to set operating parameters of different functional architectures.